2015
DOI: 10.1159/000381542
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the L-Type Amino Acid Transporter Lat2 in the Transport of 3,3′-Diiodothyronine across the Plasma Membrane

Abstract: Thyroid hormones are transported across cell membranes by transmembrane transporter proteins, for example by members of the monocarboxylate transporter (MCT) and the L-type amino acid transporter (LAT) families. LATs consist of a light chain (e.g. LAT2) and a heavy chain (CD98), which is essential for their cell surface expression and functionality. The specificity of Lat2 for thyroid hormones and their metabolites and its role in their transport was not fully clear. This fact motivated us to establish a cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Results of the study of T 3 transport in DCs in the presence of selective MCT10 and LAT2 inhibitors strengthen the main role of MCT10 in T 3 transport in DCs. In agreement, it was reported that LATs exhibit lower affinity than MCTs to transport THs (Friesema et al 2005) and a recent report revealed that LAT2 exhibits favored affinity for 3,3′-diiodothyronine (T 2 ), less for T 3 and no affinity for T 4 (Kinne et al 2015), reinforcing the evidence that LAT2 is not compelling for T 3 crossing through DC's membrane. Noteworthy, it was reported that MCT10 transports T 3 and T 4 in and out of cells (Friesema et al 2008), but it was suggested that it plays a prominent role in T 3 efflux (Muller et al 2014).…”
Section: :2supporting
confidence: 78%
“…Results of the study of T 3 transport in DCs in the presence of selective MCT10 and LAT2 inhibitors strengthen the main role of MCT10 in T 3 transport in DCs. In agreement, it was reported that LATs exhibit lower affinity than MCTs to transport THs (Friesema et al 2005) and a recent report revealed that LAT2 exhibits favored affinity for 3,3′-diiodothyronine (T 2 ), less for T 3 and no affinity for T 4 (Kinne et al 2015), reinforcing the evidence that LAT2 is not compelling for T 3 crossing through DC's membrane. Noteworthy, it was reported that MCT10 transports T 3 and T 4 in and out of cells (Friesema et al 2008), but it was suggested that it plays a prominent role in T 3 efflux (Muller et al 2014).…”
Section: :2supporting
confidence: 78%
“…In recent studies we showed that Lat2 is involved in 3,3Ј-T 2 and to lower extent in T 3 uptake (36).…”
Section: Discussionmentioning
confidence: 87%
“…It has been reported that LAT1 transports 3,3Ј-diiodothyronine (3,3Ј-T 2 ), T 3 , and rT 3 (7,(33)(34)(35). We have recently shown that Lat2 transports 3,3Ј-T 2 ; transport of T 3 is less effective and rT 3 and T 4 are not transported at all (36).…”
mentioning
confidence: 96%
“…Secondary TH transporters, i.e. the large neutral amino acid transporters LAT2 and LAT4 facilitate in and efflux of TH and other substrates (8,9,10). Thus, while the preferred TH substrate of LAT2 is 3,3′-T2 (4), LAT2 also transports large neutral amino acids, amino acid-related compounds and small amino acids (11).…”
Section: Introductionmentioning
confidence: 99%